LAT2 regulates glutamine-dependent mTOR activation to promote glycolysis and chemoresistance in pancreatic cancer - Feng, Mengyu (J Exp Clin Cancer Res, 2018)
BACKGROUND: Reprogrammed energy metabolism has become an emerging hallmark of cancer in recent years. Transporters have been reported to be amino acid sensors involved in controlling mTOR recruitment and activation, which is crucial for the growth of both normal and tumor cells. L-type amino acid transporter 2 (LAT2), encoded by the SLC7A8 gene, is a Na(+)-independent neutral amino acid transporter and is responsible for transporting neutral amino acids, including glutamine, which can activate mTOR. Previous studies have shown that LAT2 was overexpressed in gemcitabine-resistant pancreatic cancer cells. However, the role of LAT2 in chemoresistance in pancreatic cancer remains uncertain and elusive. METHODS: The effects of LAT2 on biological behaviors were analyzed. LAT2 and LDHB levels in tissues were detected, and the clinical value was evaluated. RESULTS: We demonstrated that LAT2 emerged as an oncogenic protein and could decrease the gemcitabine sensitivity of pancreatic cancer cells in vitro and in vivo. The results of a survival analysis indicated that high expression levels of both LAT2 and LDHB predicted a poor prognosis in patients with pancreatic cancer. Furthermore, we found that LAT2 could promote proliferation, inhibit apoptosis, activate glycolysis and alter glutamine metabolism to activate mTOR in vitro and in vivo. Next, we found that gemcitabine combined with an mTOR inhibitor (RAD001) could reverse the decrease in chemosensitivity caused by LAT2 overexpression in pancreatic cancer cells. Mechanistically, we demonstrated that LAT2 could regulate two glutamine-dependent positive feedback loops (the LAT2/p-mTOR(Ser2448) loop and the glutamine/p-mTOR(Ser2448)/glutamine synthetase loop) to promote glycolysis and decrease gemcitabine (GEM) sensitivity in pancreatic cancer. CONCLUSION: Taken together, our data reveal that LAT2 functions as an oncogenic protein and could regulate glutamine-dependent mTOR activation to promote glycolysis and decrease GEM sensitivity in pancreatic cancer. The LAT2-mTOR-LDHB pathway might be a promising therapeutic target in pancreatic cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-018-0947-4) contains supplementary material, which is available to authorized users.